Effect of Growth Temperature on Electrical Properties of p-Gab/n-GaAs Heterointerfaces Grown by Metalorganic Chemical Vapour Deposition. - Agus Subekti (Institut Teknologi Bandung, 2003)
Electrical characterization of heterojunction diodes between p-GaSb/n-GaAs grown by metalorganic chemical vapour deposition have been investigated. At growth temperatures of 540oC and 580oC, the interface region of GaAs show n-type doping level of 5 × 1017 and 2 × 1018 cm-3, respectively. The heating process during GaSb growth was likely responsible for the change of the doping level of the sub-surface region in GaAs due to the loss of stochiometry at the GaAs surface. This doping changes the apparent barrier heights, as well as the interface band diagram. Distinct differences appear between diodes grown on the two sides of the growth window, at 540oC and at 580 oC, with the barrier height changing from 0.92 eV to 0.29 eV.